Kendala Implementasi Sistem Rujukan Terintegrasi (Sisrute) di Indonesia - Yuni Riyanti (Pusat Riset dan Inovasi Nasional, 2023)
An integrated referral system (Sisrute) is an internet-based technology that connects patient data from lower service levels to higher or equivalent service levels (horizontally or vertically) to simplify and speed up the referral process. Sisrute has been officially implemented since 2016 but there are still limited studies on Sisrute implementation. The purpose of this study is to find out the limits of introduction of Sisrute in Indonesia. The author conducted a literature review based on journals and conference papers in the last 5 years (2018-2023). There were 8 articles that met the inclusion criteria. The results of the review found that Sisrute implementation constraints consisted of 3 aspects, namely organization or governance, human resources (users), and application system features. The organizing aspect includes leadership commitment; person responsible; reporting and evaluation; standard operating procedure and special Sisrute team; Sisrute referral acceptance flow; supporting facilities; Sisrute information media; referral hospital commitment; and update of Sisrute component information data. User aspects include response time or speed of response from referral hospitals; completeness of referred patient data; system use skills and training; as well as user perceptions regarding convenience, interest, benefits and supporting circumstances. Aspects of application systems include server or network issues; appearance and completeness of system components; mobile version system features; and utilization of application features.